Current airframe manufacturing technologies in the aeronautical industry and trends for future developments - Vieira, Paulo António Gouveia (2014)
Submitted by Joana Lopes Dias (jdias@ubi.pt) on 2014-07-18T08:20:57Z No. of bitstreams: 1 Dissertação Mestrado Engenharia Aeronáutica Paulo Vieira nº28243.pdf: 1790567 bytes, checksum: e5dd569a76a2698b9a80670d1645ad51 (MD5)